Implementation of stellarator of Costa Rica 1 SCR-1 - Vargas-Blanco, Ivan; Otárola-Zúñiga, Carlos; Zamora-Picado, Esteban; Mora-Meléndez, Jaime; Mora, A; Asenjo, J.; Villalobos, E (26th IEEE Symposium on Fusion Engineering, SOFE 2015, 2015)
The SCR-1 is a small modular stellarator designed, constructed and is being implemented at Instituto Tecnológico de Costa Rica. The project is its final phase of commissioning and it is expected to be operational in June 2015. This article aims at summarizing the SCR-1 project from the engineering and manufacturing point of view, particularly highlighting the construction of the toroidal vacuum vessel and the modular coils.
Conferencia
Keywords: Magnética; Ingeniería; Bobinas; Plasma; Fusión nuclear; Research Subject Categories::TECHNOLOGY::Engineering physics::Plasma physics with fusion